Evaluating the Usability of a Book Stock and Sales Recording Android App: System Usability Scale (SUS), Heuristic Evaluation, and Maze Tool Insights - Najaf, Abdul Rezha Efrat; Permatasari, Reisa; Sakti, Ciptagusti Sila (Journal of Information System and Informatics, 2024)
The implementation of digitalization in organizations is needed to apply technology and provide more value to customers. However, digitization still needs to be fully maximized in manually recording book stocks to record book stocks. Printed books are recorded as incoming books, sold books are sold as outgoing books and incoming and outgoing data are matched. Publishers still use Google Sheets as the primary tool for recording available book stock. However, human error, such as writing or data entry, often leads to inaccurate book stock information. Therefore, Peneleh Publishing needed an application prototype design using usability testing to identify usability issues in UI/UX development. During usability testing, the Maze tool collects user interaction data. This study used heuristic evaluation to find and solve usability problems in book sales and stock recording applications. According to the research results, the SUS score 85.2 falls into the Very Good and Acceptable category. In addition, as shown by the Tool Maze analysis, users can manage scenarios well. Experts used heuristic evaluation to suggest display improvements, pop-up notifications when books are added or subtracted, and information about successful or unsuccessful actions.